1987
DOI: 10.1136/thx.42.11.885
|View full text |Cite
|
Sign up to set email alerts
|

Phrenic nerve stimulation in normal subjects and in patients with diaphragmatic weakness.

Abstract: Phrenic nerve stimulation is often considered to be difficult and unreliable. The time taken for the phrenic nerves to be located and adequately stimulated was measured in 110 subjects, aged 21-89 years, 26 of whom had diaphragmatic weakness; and phrenic nerve conduction time was recorded in 76 of these individuals. Each phrenic nerve was stimulated transcutaneously in the neck with square wave impulses 0 I ms in duration at 1 Hz and 80-160 volts while diaphragmatic muscle action potentials were recorded with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
48
0
4

Year Published

1992
1992
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 83 publications
(59 citation statements)
references
References 13 publications
7
48
0
4
Order By: Relevance
“…However, it can be difficult to perform. The time taken to locate the phrenic nerve with ES can be up to 20 min [9]. MIER et al [9] found that the phrenic nerve could not be located with ES in some subjects, especially patients with diaphragm weakness.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, it can be difficult to perform. The time taken to locate the phrenic nerve with ES can be up to 20 min [9]. MIER et al [9] found that the phrenic nerve could not be located with ES in some subjects, especially patients with diaphragm weakness.…”
Section: Discussionmentioning
confidence: 99%
“…The time taken to locate the phrenic nerve with ES can be up to 20 min [9]. MIER et al [9] found that the phrenic nerve could not be located with ES in some subjects, especially patients with diaphragm weakness. Repeated stimulation for 30 min has been required to establish a diagnosis of diaphragm paralysis with reasonable confidence in the absence of a CMAP response to ES [9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conclusão: O melhor ponto de estímulo do nervo frênico no pescoço varia entre a borda medial e lateral da cabeça clavicular do músculo esternocleidomastóideo. Estimular ambos os locais e escolher a melhor resposta do nervo frênico parece ser o procedimento mais adequado.Palavras-chave: eletrodiagnóstico; valores de referência; nervo frênico; espirometria; condução nervosa.Phrenic nerve conduction has found increasing application in the diagnosis of respiratory dysfunction associated with surgical, neuromuscular, and pulmonary disorders 1,2,3,4,5,6 , which are important causes of respiratory failure and frequently contribute to difficulties in weaning patients off the ventilator in the critical care unit 7 . To determine a neuromuscular cause of hypercapnic respiratory failure, respiratory electrodiagnostic studies are often used 8 .…”
unclassified
“…Phrenic nerve conduction has found increasing application in the diagnosis of respiratory dysfunction associated with surgical, neuromuscular, and pulmonary disorders 1,2,3,4,5,6 , which are important causes of respiratory failure and frequently contribute to difficulties in weaning patients off the ventilator in the critical care unit 7 . To determine a neuromuscular cause of hypercapnic respiratory failure, respiratory electrodiagnostic studies are often used 8 .…”
Section: Introductionmentioning
confidence: 99%